ANDRIĆ I JOVKOV – IZMEĐU IRONIJE I IDEALIZACIJE - Bijelić, Marijana (Philological Studies, 2019)
Certain similarities between the works of Ivo Andrić and Jordan Jovkov have already been noted by some Bulgarian literary historians since both authors combine the elements of traditional realistic narration with some modern features. Novels Ćorkan and Švabica by Ivo Andrić and Private teacher by Jordan Jovkov share some similarities on the level of the plot but it is more important that both of them unite elements of idealistic and ironic mode of narration. Although Jovkov’s novel is more traditional from the aesthetic point of view, the relationship of gender identities is more modern - it rejects traditional heroic male identity and affirms the idea of a strong woman who saves a vulnerable man. In Andrić’s novel the idea of idealized femininity and the aspirations of the main character toward heroic are strongly ironized, but the relationship between traditional gender roles is not put into question. Both novels contain certain experience of epiphany, which, together with the pathos, has the main role for the (re)affirmation of the idealistic mode.